Framework for Considering Abnormal Heart Rate Characteristics and Other Signs of Sepsis in Very Low Birth Weight Infants - Kumar, Rupin S.; Otero, Noelia Aviles; Abubakar, Maryam O.; Elliott, Megan R.; Wiggins, Jaclyn Y.; Sharif, Misky M.; Sullivan, Brynne A.; Fairchild, Karen D. (American Journal of Perinatology, 2022)
Objective A heart rate characteristics index (HeRO score), incorporating low variability and superimposed decelerations, was developed as a sepsis risk indicator for preterm infants in the neonatal intensive care unit (NICU). A rise in the risk score should prompt consideration of other clinical changes that may be signs of sepsis to decide whether a workup and antibiotics are needed. We aimed to develop a framework to systematically consider signs potentially indicating sepsis in very low birth weight (VLBW) infants.Study Design We developed easy-recall acronyms for 10 signs of sepsis in VLBW infants. Over 12 months in a level IV NICU, neonatology fellows completed a brief survey after each shift to document changes prompting sepsis workups. We analyzed associations between survey data, hourly heart rate characteristic data, and the diagnosis of the workup, grouped as culture-positive sepsis (CXSEP, positive blood or urine culture), clinical sepsis (CLINSEP, negative cultures treated with antibiotics ≥5 days), or sepsis ruled out (SRO, negative cultures and <3 days antibiotics).Results We analyzed 93 sepsis workups in 48 VLBW infants (35 CXSEP, 20 CLINSEP, and 38 SRO). The most frequently cited changes prompting the workups were heart rate patterns and respiratory deterioration, which were common in all three categories. Low blood pressure and poor perfusion were uncommonly cited but were more likely to be associated with CXSEP than the other signs. A rise in the HeRO score ≥1 from 0 to 12 hours before compared with 12to 72 hours prior the blood culture occurred in 31% of workups diagnosed as CXSEP, 16% CLINSEP, and 31% SRO.Conclusion The HeRO score can alert clinicians to VLBW infants at high or increasing risk of a sepsis-like illness, but heart rate characteristic patterns are highly variable in individual babies. The easy-recall NeoSEP-10 framework can assist clinicians in considering other clinical changes when making decisions about sepsis workups and the duration of antibiotics.Key Points
Keywords: Late-onset sepsis; neonatal sepsis; prematurity; clinical signs; vital signs